2011
DOI: 10.1039/c0cc02075c
|View full text |Cite
|
Sign up to set email alerts
|

Implications of citrate concentration during the seeded growth synthesis of gold nanoparticles

Abstract: Increasing the citrate concentration during the seeded growth synthesis of gold nanoparticles yields materials with decreased aspect ratios and increased defect densities. The stability of these nanoparticles is attributed to variations in their overall Gibb's free energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 17 publications
0
47
1
1
Order By: Relevance
“…Previous works reported that colloidal solutions of gold nanoparticles synthesized using sodium citrate are stable for at least one year. 26,29 The concentration of gold nanoparticles in the AuNP colloidal solution was determined from the ICP-MS data and it is shown in Table 1. This concentration was estimated from the total amount of gold found in the bottom of the tube after the centrifugation procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Previous works reported that colloidal solutions of gold nanoparticles synthesized using sodium citrate are stable for at least one year. 26,29 The concentration of gold nanoparticles in the AuNP colloidal solution was determined from the ICP-MS data and it is shown in Table 1. This concentration was estimated from the total amount of gold found in the bottom of the tube after the centrifugation procedure.…”
Section: Resultsmentioning
confidence: 99%
“…It can be concluded that the higher ionic strength as a result of high molarities of HAuCl 4 leave a significant impact on the size of gold nanoparticles obtained. [28] Effect of concentration of PRX-MEA on Particle size and loading efficiency…”
Section: Effect Of Gold Salt Concentration On Particle Size and Loadimentioning
confidence: 99%
“…Like citrate, exploitation of tannic acid (a plant derived polyphenol) as a reductant and stabilizer in the synthesis of gold nanoparticles dates back to early 20 th century [22,23] but citrate in the past few decades enjoys an extra edge over tannic acid (TA) as an agent for GNPs synthesis. Overwhelming amount of literature is available for the effect of citrate concentration [24], pH [25], temperature [26] and gold chloride concentrations [22] on the characteristic properties of GNPs synthesized using citrate as reductant. However, similar studies on the GNPs synthesized exploiting TA have not been much explored and our knowledge on this subject remains in its infancy.…”
Section: Introductionmentioning
confidence: 99%